PENGARUH WORK FAMILY CONFLICT, BEBAN KERJA DAN STRES KERJA TERHADAP KINERJA PERAWAT RUMAH SAKIT UMUM DAERAH (RSUD) KABUPATEN KOLAKA TIMUR - Mubaraq, Ahmad; Syarif, Muhammad (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to analyze the influence of work family conflict, workload, and work stress on nurse performance at East Kolaka Regency Hospital, both simultaneously and partially. The research method uses a quantitative approach with a causal associative design. The research population consisted of 37 female nurses who were married and working in the service department, sampled using total sampling technique. Data collection used a 5-point Likert scale questionnaire that had been tested for validity and reliability. Data analysis employed multiple linear regression after meeting classical assumption tests. The results showed that work family conflict, workload, and work stress simultaneously had a significant effect on nurse performance. Partially, all three variables had a negative and significant effect on nurse performance, with work family conflict as the most dominant factor. The contribution of these three variables to nurse performance was 33%. This research recommends developing comprehensive HR management policies to manage these three factors in order to improve nurse performance and healthcare service quality.